Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.